(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The assessment of the degree of radical removal of brain meningiomas from the moment of surgery was assessed by the frequency and timing of recurrence, continued growth, depending on the degree of radical removal of tumors, their location, and the presence of altered underlying bone (hyperostosis). The incidence of tumor recurrence 5 years after radical surgical treatment is 56-78%. However, the main clinical and surgical significance are such properties of meningiomas as invasiveness of growth, degree of malignancy and ability to metastasize.